Measuring teachers' knowledge of student assessment: Development and validation of an MCQ test. Issue 1 (2nd January 2023) - Iqbal, Zafar; Saleem, Khalid; Arshad, Hafiz Muhammad
ABSTRACT: To improve the teaching-learning processes, the Government of Pakistan and UNESCO developed professional standards for teachers to standardise student assessments based on assessment types, use of assessment results, measurement theories, and assessment-related issues. Most tools developed for measuring teachers' knowledge of student assessment do not cover these aspects. Therefore, this study aims to develop and validate an MCQ test for quantifying teachers' knowledge of these aspects. A test consisting of 34 components was designed and administered to 1624 elementary school teachers. The test's validity and reliability were measured using a difficulty index, a discrimination index, distractor efficiency, and the Kuder and Richardson Formula 20 ( ρ K R 20 ). Per the results, 31 items were found to be appropriate, three items rated poorly on the discrimination index, and, of these, two were rated too difficult according to the difficulty index. The estimated value of ρ K R 20 was 0.75, indicating appropriate reliability of the test.